Semantic Marking in Javanese: A Study of Language Typology - Bhrata, Pramudya Dhana; Khoironi, Haris; Mahbub, Moh Tarojjil (Translation and Linguistics (Transling), 2025)
This study aims to classify the use of semantic marking in the Javanese language. It employs a qualitative descriptive approach. Specifically, this research analyzes marking based on syntactic principles, semantic principles, or a combination of both (syntactic and semantic), demonstrating that a portion of Javanese grammar utilizes semantic marking. The data in this study consist of Javanese utterances that contain semantic marking. The data sources are multiple, as the research involves more than one source, including books, relevant articles, and others. The data were collected using an observation method with a note-taking technique, followed by critical discourse analysis as an advanced technique. The data analysis technique involves three stages: data reduction, data presentation, and conclusion drawing. The results of this study indicate that some of the findings include active-passive processes (transitive becoming intransitive) in Javanese, contrastive comparison marking (controlled vs. uncontrolled) from various perspectives, such as affixation (prefix ke-, prefix m-, or infix -em), argument shifts from SO to SA and vice versa, and others.  The implications of this study are expected to demonstrate the role of semantic meaning patterns marked in words, phrases, and clauses in Javanese through affixation, particles, or sentence structure changes.